Analisis Kualitas Pelayanan Menggunakan Metode Servqual: Studi Kasus di Perpustakaan Unesa - Gloriano Gloriano; Jaka Nugraha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
Libraries are one of the tools or facilities to support a student's learning process. Libraries provide information in books, articles, journals, educational reports and other documents. The information that can be obtained by library users can be text, books and online journals accessible through the Internet. Surabaya state university has provided facilities such as the library, in an effort to meet the needs of students in the academic field. However, the purpose of the study was to learn the student's satisfaction with service provided by the surabaya state university library. The study USES servqual methods to measure student satisfaction levels based on the quality of library services provided by analyzing expected performance/reality and expected value, and the quality of the surabaya state university library service. The population of this research is Office Administration Education students class of 2017, totaling 81 people. Testing instruments in this study consisted of validity testing and reliability testing. The data analysis technique used in this research is the servqual formula. The results of this study indicate that: the results of the average student satisfaction obtained from measuring the five dimensions of Servqual are still not satisfied with the quality of services provided, it is indicated by the average value of student satisfaction which is negative